RENTAL APPLICATION PROGRAM DESIGN DVD RENTAL 'MYDISC "USING MICROSOFT VISUAL BASIC 6.0 - Suwarno Suwarno; Erick Orlando, SKom., MMSI (Jurnal Sistem Informasi, 2008)
In this scholarly writing explain about the making of the DVD rental applicationprograms using Visual Basic 6.0 programs consist of the login form, the form MainMenu, the form the customer, the form Rental Transactions, Customer Reports andforms can be printed.Then, making this application utilizing Microsoft Access database in the facility andworks under windows operating system to facilitate the making of this program.Lease is an agreement or agreements in which the tenant must pay or providecompensation or benefits from the objects or goods owned by the owner of the loaneditems. Example of a lease in everyday life such as office building contract hire, leaseland for agricultural land, hire / cha rter vehicles, rentals vcd and dvd original, and soforth.